Perhitungan Pajak Penghasilan Pasal 21 ( PPh Pasal 21) Atas Gaji Pegawai Tetap Pada Balai Pelatihan Dan Penyuluhan Perikanan (BPPP) Ambon - Latuamury, Sherlie Evabioni (ISAS, 2024)
The aim of this research is to calculate Income Tax Article 21 on the salaries of permanent employees of the Ambon Fisheries Training and Extension Center for employees of class II, class III, and class IV for the 2023 tax year following Minister of Finance Regulation Number 40/PMK.03/2017 concerning Reporting Procedures and Calculation of Income Tax Article 21 on Employee Income from Employers with Certain Criteria.The research uses quantitative methods with secondary data in the form of salary data for permanent employees of the Ambon Fisheries Training and Extension Center for class II, class III, and class IV employees in December 2023. After calculating PPh Article 21 tax on the salaries of permanent employees of the Training and Extension Center Ambon Fisheries (BPPP) where the author calculates the salaries of employees from each group. namely class II, class III, and class IV employees. The results of the research show that group II employees, in this case PTKP as taxpayers, are greater than the total annual net income, so the PPh is nil or not subject to deductions from PPh Article 21 on salaries, group III, in this case as taxpayers, is greater than the amount annual net income, then group III tax is nil or is not subject to deductions from PPh Article 21 on salary. and employees of class IV PPh article 21 whose monthly deduction is IDR 55,180.4 Keywords: income tax article 21, permanent employees.